EMOTIONAL REGULATION AMONG ENGLISH STUDENTS IN FACING ACADEMIC PRESSURE - Dedy Wahyudi; Fatma Insania Sakinah; Nur Ismi Ramadhani; Mhd Hafidz Ridho (Consilium: Education and Counseling Journal, 2026)
This study aims to examine emotional regulation among English department students in dealing with academic pressure. Academic pressure is a common condition experienced by students due to assignments, examinations, presentations, and the demands of mastering English language skills actively. These conditions may trigger various negative emotions such as anxiety, frustration, and stress, which can affect the learning process. This study employs a literature review method by analyzing various academic sources, including books, journals, articles, and previous studies relevant to the topic. The data were analyzed descriptively to obtain an overview of the forms of academic pressure, students' emotional responses, and the strategies they use to regulate their emotions. The findings show that English students apply several emotional regulation strategies, such as time management, social support, and relaxation activities, to cope with academic pressure. Effective emotional regulation helps students maintain focus, improve learning motivation, and support academic achievement. In contrast, poor emotional management may negatively affect academic performance and mental health. Therefore, emotional regulation is an important aspect in supporting students' academic success. Keywords: Emotional Regulation, English Students, Academic Pressure